Postglacial vegetation community change over an elevational gradient on the western Kenai Peninsula, Alaska: pollen records from Sunken Island and Choquette Lakes. (12th July 2019) - Scott Anderson, R.; Berg, Edward; Williams, Chris; Clark, Tami
Abstract: The Kenai Peninsula of south‐central Alaska is a region of high topographic diversity with a complex glacial history. The sedimentary record of two small lakes [Sunken Island (SIL; 76 m a.s.l.) in the Kenai Lowlands; Choquette (CL; 527 m a.s.l.) in the Caribou Hills upland] exemplifies the postglacial development of the conifer–hardwood forest over an elevational range there. A herb–shrub tundra was established at both sites after deglaciation. By ~10.7 ka, poplar ( Populus sp.) and alder ( Alnus ) dominated the lowland forest, while alder with minor poplar occurred at the upland site. Lake levels lower than today occurred during the early Holocene until ~8 ka. Subsequently at SIL, the near‐modern Kenai birch ( Betula kenaica ) – white spruce ( Picea glauca ) forest maintained prominence throughout the Holocene. However, at CL, alder dominated with dwarf birch and other subshrubs; small amounts of white spruce arrived ~5.2 ka. Black spruce ( Picea mariana ) grew around SIL by ~4 ka, but never gained prominence at CL. Fire, a prominent agent of disturbance in the Kenai Lowlands since ~8 ka, was essentially absent at the hardwood‐dominated upland site before ~6 ka, and rare thereafter. This suggests an important link between fire and spruce in Kenai forests.